Proteolytic activity of human cytomegalovirus UL80 protease cleavage site mutants. - Jones, T R (1994)
The human cytomegalovirus UL80 open reading frame encodes protease and assembly protein from its N- and C-terminal regions, respectively. We reported previously that a 30-kDa protease is derived by autoproteolytic processing of a polyprotein which is the translation product of the entire UL80 open reading frame (E. Z. Baum, G. A. Bebernitz, J. D. Hulmes, V. P. Muzithras, T. R. Jones, and Y. Gluzman, J. Virol. 67:497-506, 1993). Three autoproteolytic cleavage sites within the UL80 polyprotein were characterized; site 143 is within the protease domain and inactivates the protease. In this article, we report (i) expression analyses of UL80 in infected cells, including the processing kinetics of the UL80 polyprotein; (ii) the existence of an additional cleavage site (site 209) within the protease domain of the UL80 polyprotein; and (iii) the effect of mutagenesis at each of the cleavage sites upon proteolytic activity and steady-state levels of the UL80 processing products. During the course of infection, UL80 polyprotein processing begins at cleavage site 643 and follows at sites 256 and 143. Cleavage at site 643 and/or 256 within the polyprotein is not a prerequisite for efficient protease activity, since all three proteases (85-, 80-, and 30-kDa proteins) were equally active in cleaving the assembly protein precursor to its mature form. Inhibition of cleavage at site 143 resulted in a three- to sixfold increase in the steady-state level of the 30-kDa protease, supporting the hypothesis that cleavage at this site may represent a mechanism by which cytomegalovirus regulates the level of active protease.